Quality of life and urban environment. Local sustainability indicators and quality of urban life - Hernández Aja, Agustín (Revista INVI, 2009)
This article begins with the premise that the sustainahility paradigm demands a system of ascertainment and assessment of objectives and sustainahility programs as systems' indicators. For this purpose sets sustainahility within the Quality of Urban life framework. It describes the different indicators using local sustainahility indicators analysis examples from Agendas 21 of the Spanish Municipalities. It ends with a comment on the city conception as satisfier, proposing a system of indicators that goes beyond the sectorial urban indicators usage.